Normative Juridical Study of Regulatory Urgency Use of Local Labor in the Regions: Normative Juridical Study of Regulatory Urgency Use of Local Labor in the Regions - Simarmata, Jorawati (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
Indonesia, in the context of